Uji Toksisitas Akut Ekstrak Etanol Daun Alpukat (Persea americana Mill.) dan Pengaruhnya Terhadap Hepar Mencit BALB/c: Acute Toxicity Testing of The Ethanol Extract of Persea americana Mill. and Its Influence on The Hepars of BALB/c Mice - Ririn, Ririn Lispita Wulandari; Pamungki, Wicaksaning Dyah; Ningsih, Fitri Mustiko (Universitas Tidar, 2024)
Avocado leaf ethanol extract as a traditional medicine has been proven to have various pharmacological activities, but the safety of its use is not yet known. This study aims to determine the range of LD50 values, toxic symptoms, changes in body weight, and SGPT SGOT levels of Balb/c mice. The research was carried out experimentally using a fixed dose toxicity test method with a randomized matched pre and post-test control group design. EEDA is made by 70% ethanol maceration. The acute toxicity test consists of 2 stages: preliminary and main tests. Preliminary tests were carried out with a dose of extract 300 mg/kg BW once administered. After 24 hours of observation, there were no toxic symptoms, the test dose was increased to 2000 mg/kg BW. The main test was carried out using 10 test animals which were divided into 2 groups, each given a dose of extract 2000 mg/kg BW once and CMC Na 1% (negative control). Observation of toxic symptoms and death was carried out for 14 days. The LD50 value is determined from the results of toxic symptoms and death of test animals. Toxic symptoms were analyzed descriptively, and changes in body weight and SGOT SGPT levels were analyzed statistically (95% confidence level). The research results show that avocado leaf ethanol extract has an LD50 value range of >2000 mg/kg BW. The test dose of 2000 mg/kg BW did not cause toxic symptoms and death. SGOT and SGPT levels were still within normal limits, however, changes in SGPT levels were significantly different from controls. Thus, an extract dose of 2000 mg/kg BW has an acute toxic effect on the liver of mice.